Promoting the well-being of rural elderly people for longevity among different birth generations: A healthy lifestyle perspective - Li, Xian; Gao, Min; Chu, Meijie; Huang, Shiling; Fang, Zhiwei; Chen, Tianmu; Lee, Chun-Yang; Chiang, Yi-Chen (Frontiers in Public Health, 2023)
Background: Well-being may have a protective role in health maintenance. However, no specific study clarified the particular protective effect of the subjective well-being of rural elderly people on survival probability. Few studies have examined the effect of the lifestyle of rural elderly people on their subjective well-being from different perspectives. We investigated whether improving subjective well-being increased the probability of longevity of rural elderly people and the effects of lifestyle behaviors on the subjective well-being of rural elderly people in different birth generations. Materials and Methods: Data were derived from the China Health and Nutrition Survey (CHNS), which is an ongoing open cohort study that adopts a multistage, random clustered sampling process. We used the data of elderly people who were aged 65 or over during 2006–2015 for analysis. The Kaplan‒Meier method and log-rank test found that the survival probability of rural elderly people was significantly lower than urban elderly people. Based on a sample of rural elderly people, Cox regression and generalized estimating equations were performed as further analyses. Results: A total of 892 rural elderly people aged 65 or over were included in the sample in 2006. High subjective well-being was a protective factor against death. The subjective well-being of rural elderly people born in the 1940s/1930s/1908–1920s birth generations first decreased then increased. For rural elderly people born in the 1940s, there were significant positive effects of a preference for eating vegetables and walking/Tai Chi on subjective well-being. For rural elderly people born in the 1930s, preferences for eating vegetables, reading, and watching TV all had significant positive effects on subjective well-being. Rural elderly people born in the 1908–1920s who preferred watching TV had more subjective well-being. Conclusion: Improving subjective well-being extended the life span and reduced mortality risk in rural elderly people and may be achieved by the shaping of a healthy lifestyle, such as preferences for eating vegetables, walking/Tai Chi, and reading.